Wolność sumienia i religii w Konstytucji Rzeczypospolitej Polskiej - postulaty Kościoła katolickiego - Sobczyk, Paweł (Prawo Kanoniczne, 2008)
The systemic transformation initiated by the Roundtable talks of 1989 made it necessary for Poland to amend its constitution, including the regulations concerning the freedom of conscience and religion. It was natural for churches and religious organisations, including the Catholic Church, to participate in the constitutional debate. The study, reflecting only the Catholic Church’s official positions, presents issues concerning the Catholic Church’s position on religious freedom in the individual dimension, that is, the freedom of conscience and religion. The Conference of the Polish Episcopate’s 1990-1997 positions on religious freedom in the individual dimensions contained some of the most important aspects of the teaching of the Second Vatican Council. These represented the basis of the Episcopate’s position in the several-year-long debate on the desired model of the state. The constitutional guarantees of religious freedom contained in the article 53 (freedom of conscience and religion) should be seen as a compromise between the principles of liberal ideology and the teachings of the Vaticanum II.